2021
DOI: 10.3174/ajnr.a7232
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in the Magnetoencephalography Default Mode Effective Connectivity following Concussion

Abstract: BACKGROUND AND PURPOSE: Magnetoencephalography is sensitive to functional connectivity changes associated with concussion. However, the directional influences between functionally related regions remain unexplored. In this study, we therefore evaluated concussion-related magnetoencephalography-based effective connectivity changes within resting-state default mode network regions. MATERIALS AND METHODS:Resting-state magnetoencephalography was acquired for 8 high school football players with concussion at 3 time… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…Participants with subacute concussion showed symmetrical bilateral patterns with reduced central-parietal activity and additional frontal-temporal connections. Another study found increased posteriorto-anterior effective connectivity following concussion in sample of male high school football players (34). In a pediatric case-control sample, post-concussion effective connectivity within the DMN showed increased inter-and intra-hemispheric anterior connectivity, with unique connections from the orbitofrontal cortex to parietal regions (35).…”
Section: Introductionmentioning
confidence: 94%
See 2 more Smart Citations
“…Participants with subacute concussion showed symmetrical bilateral patterns with reduced central-parietal activity and additional frontal-temporal connections. Another study found increased posteriorto-anterior effective connectivity following concussion in sample of male high school football players (34). In a pediatric case-control sample, post-concussion effective connectivity within the DMN showed increased inter-and intra-hemispheric anterior connectivity, with unique connections from the orbitofrontal cortex to parietal regions (35).…”
Section: Introductionmentioning
confidence: 94%
“…A limited number of causal connectivity analyses have been employed in concussed populations (33)(34)(35)(36)(37). We previously investigated causal connectivity in a sample of adolescent male hockey players, finding significant differences between those with subacute concussion and healthy controls (33).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have found increased levels of connectivity deemed “hyperconnectivity.”28 Magnetoencephalography (MEG) has been utilized to demonstrate support of the hyperconnectivity hypothesis in mild TBI, reporting increased connection strength in several frequency ranges in the DMN29,30 as well as the rich club 31. Other studies have found decreased levels of connectivity associated with mild TBI or mixed results based on the region examined 32–34…”
mentioning
confidence: 99%
“…31 Other studies have found decreased levels of connectivity associated with mild TBI or mixed results based on the region examined. [32][33][34] Results describing the effect of TBI on the strength of connectivity and the organization and topology of the functional connectome are mixed. This is potentially a result of studies varying by sample population (eg, civilian, veteran, mixed severities), time since injury, methods utilized, and the technology employed.…”
mentioning
confidence: 99%